Exploring the variations in death anxiety among oncology nurses in China: a latent class analysis - Xian Chen; Mengyu Su; Anne Arber; Chengping Qiao; Jinfeng Wu; Cuihua Sun; Dan Wang; Hui Zhou; Zhu Zhu (BMC Palliative Care, 2023)
Abstract Background Various factors have been found to be associated with high levels of death anxiety experienced by oncology nurses. The aim of this study was to use a person-oriented approach to examine the death anxiety patterns of Chinese oncology nurses and to analyze the differences in anxiety characteristics and their associated influencing factors. Methods A cross-sectional survey regarding palliative care among registered oncology nurses was conducted in Jiangsu Province, China.Latent class analyses was applied to identify their patterns of death anxiety. The score of PCQN-C (The Chinese version of the Palliative Care Quiz for Nursing) and FATCOD-B-C (The Chinese version of the Frommelt Attitude Toward Care of the Dying scale), the demographic and working characteristics were further analyzed through covariance analysis (ANCOVA) and multivariate (or logistic) regression across the subgroups. Results A two-potential-category model was selected based on the fit index. The results showed that 79% of oncology nurses belonged to the high pressure and pain group and 21% belonged to the low death anxiety group. The high pressure and pain group had significantly higher scores in the dimensions of emotion, stress and pain, time awareness, and cognition compared to the low death anxiety group. Factors influencing the high pressure and pain group included shorter working years, non-national or provincial oncology nursing specialists, non-national palliative care specialists, never discussing the topic of death with patients or family members, no palliative care related training, and PCQN and FATCOD scores. Conclusions Our study suggests that oncology nurses’ death anxiety can be divided into two categories: low death anxiety and high stress pain, and certain factors, such as being female, having a short work experience, and lacking palliative care-related training, increase the likelihood of death anxiety.